Leadership standpoints : a practical framework for the next generation of nonprofit leaders - Waisanen, Don (Cambridge elements. Elements in public and nonprofit administration,, 2021)
This project offers a new leadership framework for the next generation of nonprofit professionals. Based on five years of data collected from the New York Community Trust Leadership Fellowship - designed to address leadership development gaps in the nonprofit sector - it constructs three dimensions and eleven themes for the theory and practice of leadership standpoints. Leadership standpoints are a framework for practicing inclusion, building spaces for performance, and thinking and acting with range. Those using leadership standpoints continuously interact with diverse stakeholders, constantly verify others' views and interests, and remain keenly attentive to power distributions, material constraints, and hidden or unacknowledged voices that need surfaced, while expanding their personal and social outlooks to elevate performance and meet pressing demands best addressed through broadly informed decisions. This title is also available as Open Access on Cambridge Core.